2016
DOI: 10.4103/2230-8229.189132
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress and associated factors among medical students

Abstract: Background:Stress and its psychological manifestations are currently a major source of concern. Medical education poses challenging and potentially threatening demands for students throughout the world.Objectives:To determine the prevalence and factors associated with perceived stress in medical students in the College of Medicine, King Saud Bin Abdulaziz University for Health Sciences, King Fahad Medical City, Riyadh, Saudi Arabia.Materials and Methods:This was a cross-sectional study on all medical students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
80
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 26 publications
(33 reference statements)
10
80
3
3
Order By: Relevance
“…Another study found males to be more stressed than females, a difference which the authors argue may be due to male students' increased need to have high scores and complete their programs as quickly as possible in order to start their careers (Abdel Rahman, Al Hashim, Al Hiji, & Al-Abbad, 2013). Most studies, including the present study, found that females reported much higher levels of stress than males (Abdulghani, AlKanhal, Mahmoud, Ponnamperuma, & Alfaris, 2011;Saeed et al, 2016). The inconsistency of gender association with stress among medical students may be to the result of differences in social and educational environments, as well as of subjectivity in measuring self-reported stress.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Another study found males to be more stressed than females, a difference which the authors argue may be due to male students' increased need to have high scores and complete their programs as quickly as possible in order to start their careers (Abdel Rahman, Al Hashim, Al Hiji, & Al-Abbad, 2013). Most studies, including the present study, found that females reported much higher levels of stress than males (Abdulghani, AlKanhal, Mahmoud, Ponnamperuma, & Alfaris, 2011;Saeed et al, 2016). The inconsistency of gender association with stress among medical students may be to the result of differences in social and educational environments, as well as of subjectivity in measuring self-reported stress.…”
Section: Discussionmentioning
confidence: 62%
“…The results suggest that it is not the teaching method but the medical school program itself that triggers stress, given the relatively high number of students in the near exhaustion phase in both universities. Furthermore, important causes of stress among new medical students included the large amount of new information, limits on time, competition, fear of failing grades, and social problems, all of which can result in anxiety and depression (Aguiar, Vieira, Vieira, Aguiar, & Nóbrega, 2009;Saeed, Bahnassy, Al-Hamdan, Almudhaibery, & Alyahya, 2016). However, it is necessary to establish a balance between learning styles to decrease the possibility that stress will develop (Silva, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The most common perceived sources of academic stress, reported by various medical students in the literature, include fear of examinations, concerns about examination results and grades, and fear of failing the course at the end of the semester/year. [32][33][34] The flipped exam model in our study did not just reduce test anxiety, however it also addressed academic and test competence issues, which also represent substantial components associated with academic performance. 31 For instance, academic competence, which refers to a students' ability to manage their study load, 31 was undertaken by allowing the students to employ their understanding of the workshop presentations to design one question that they perceive as essential and relevant to learning.…”
Section: A J P E a C C E P T E D D R A F Tmentioning
confidence: 99%
“…Student's gender was also linked to the higher depression and stress level; where the females showed higher stress levels than males but the difference did not reach statistical significance among medial students at King Saud Bin Abdulaziz University for Health Sciences [14].…”
Section: Introductionmentioning
confidence: 99%